Prerequisites For The Establishment Of Transport And Logistics Centres On The Basis Of Railway Stations - et. al., Aikumbekov Muslim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Kazakh and foreign economists note that the decline in industrial and agricultural production, stagflation of the economy of the Republic of Kazakhstan in the post-crisis period require a deep analysis of the current situation and careful development of appropriate economic and managerial decisions. In these circumstances, it is necessary to find the most effective ways out of the crisis.It is obvious that it makes no sense for the Republic of Kazakhstan to fully follow the centuries-old path of becoming an industrially developed country. Without a doubt, the modern market economic system should serve as a reference point, which, in addition to free competition, also has numerous internal and external levers of management and regulation, including state ones, which in their essence suppress bursts of fluctuations in the market element and allow using all the advantages and advantages of market relations.One of these ways in the market economy, according to many experts, with whom it is difficult to disagree, is the design of logistics models, the formation, implementation and organization of the rational functioning of logistics services, structures, management systems at the on-farm, industrial (micro logistics) and macroeconomic, international, national, regional (macro logistics) levels, the widespread development and application of logistics methodology, technologies and tools, creation of logistics management systems that differ in their functional purpose and organizational and economic level.When integrating the economy of the Republic of Kazakhstan into the world economic community, there is an increasing need to create reliable, dynamic and efficient domestic logistics management systems that could optimally interact with the national logistics systems of foreign countries in international economic and logistics processes at the macro - and micro logistic levels.These logistics systems are designed to facilitate the rational movement of any flows of information, goods, capital and people both within the country and across the borders of States, taking into account the national peculiarities of customs clearance and support.